1998
DOI: 10.1176/ajp.155.9.1234
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Population-Based Twin Study of Retrospectively Reported Premenstrual Symptoms and Lifetime Major Depression

Abstract: Retrospectively reported premenstrual-related symptoms of depression and anxiety are moderately stable over time and, when correction is made for this level of stability, substantially heritable. The genetic and environmental risk factors for these premenstrual symptoms and lifetime major depression are not closely related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 34 publications
5
61
1
4
Order By: Relevance
“…Kendler et al, for example, observed that premenstrual, menstrual and neurotic symptoms had different genetic and environmental determinants (Kendler et al 1992) and that the heritability of PMS was about 56% (Kendler et al 1998). These studies provide a rational basis for the search for genetic contributions to PMDD.…”
Section: Discussionmentioning
confidence: 96%
“…Kendler et al, for example, observed that premenstrual, menstrual and neurotic symptoms had different genetic and environmental determinants (Kendler et al 1992) and that the heritability of PMS was about 56% (Kendler et al 1998). These studies provide a rational basis for the search for genetic contributions to PMDD.…”
Section: Discussionmentioning
confidence: 96%
“…ER polymorphisms may also be involved in HT response, a possibility which has not yet been evaluated. The importance of family or genetic factors in the etiology of MRD or postpartum mood disorders has already been suggested [137,138]. Recently, Rubinow and Schmidt [139] have also shown that a region of the ERα gene containing multiple polymorphic alleles was associated with MRD, thus supporting the hypothesis that the effects of multiple genes may interact in creating a dysphoric behavioral response to normal gonadal steroid levels.…”
Section: Is There a Common Pattern Of Vulnerability Regarding Reprodumentioning
confidence: 90%
“…Existem evidências recentes de se tratar de um fenômeno mais biológico do que primariamente psicológico ou psicossocial. Kendler et al (1998) demonstraram que existem fatores genéticos envolvidos. Tanto a supressão temporária da atividade hormonal dos ovários como a menopausa cirúrgica estariam associadas à melhora ou eliminação das queixas pré-menstruais.…”
Section: Transtornos Associados Ao Ciclo Reprodutivo Disforia Pré-menunclassified